1973
DOI: 10.1159/000169618
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of Chronotropic Response of the Heart Through Pacemaker Stretch

Abstract: Mechanical stretch is a fundamental biological stimulus for pacemaker activity. Stretch-sensitiveness enables the heart to autoregulate its rate in relation to venous return. Phylogenetically the importance of this primitive mechanism has been diminished by the emergence of neurohumoral influences which permit a quicker and more effective adaptation of cardiac performance. Nevertheless, the intrinsic autoregulatory mechanism is capable of independent operation and may support extrinsic neurohumoral influences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
2

Year Published

1976
1976
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 24 publications
2
8
0
2
Order By: Relevance
“…In 1915, Francis Arthur Bainbridge observed that intravenous fluid injection in anaesthetised dogs resulted in right-atrial distension and an increase in BR (Bainbridge, 1915). He described this as an “ Acceleration of heart rate […] caused by impulses arising within the heart .” Similar effects have since been observed in various vertebrate phyla, including Amphibia , Reptilia , Aves , and Mammals (Pathak, 1973). Confirming this finding in humans proved difficult, initially, as most non-invasive interventions that raise central venous pressure in human (such as tilt-table studies) also increase arterial pressure.…”
Section: Direct Mechanical Effects On Cardiac Pacemaker Activitysupporting
confidence: 67%
“…In 1915, Francis Arthur Bainbridge observed that intravenous fluid injection in anaesthetised dogs resulted in right-atrial distension and an increase in BR (Bainbridge, 1915). He described this as an “ Acceleration of heart rate […] caused by impulses arising within the heart .” Similar effects have since been observed in various vertebrate phyla, including Amphibia , Reptilia , Aves , and Mammals (Pathak, 1973). Confirming this finding in humans proved difficult, initially, as most non-invasive interventions that raise central venous pressure in human (such as tilt-table studies) also increase arterial pressure.…”
Section: Direct Mechanical Effects On Cardiac Pacemaker Activitysupporting
confidence: 67%
“…Mechanical effects on the sinus node might explain the responses to tilting and Valsalva's maneuver. 4 Exercise to the maximum levels possible in our patient increased heart rate by 11 beats per minute. In the transplanted human heart the rate is barely affected by mild exercise, but during prolonged exercise the rate may increase almost as much as in the normal heart.…”
Section: Discussionmentioning
confidence: 51%
“…9,29) This result was confirmed in a largescale trial conducted by Cole, et al 6) Several mechanisms have been proposed for the attenuation of HRR in coronary artery disease patients, such as an imbalance between sympathetic withdrawal and parasympathetic activation, the alteration of venous return, or stretch in the atrial wall. [1][2][3][4][5] The mechanism underlying the attenuation of HRR in heart failure patients may be much more complicated. The decreased resting vagal tonus, increased resting and exercise sympathetic tonus, and attenuation of autonomic regulatory mechanisms by increasing age are possible mechanisms proposed for the attenuation of HRR in heart failure patients.…”
Section: Discussionmentioning
confidence: 99%